Relationship between tactical and technical performance in youth soccer players - Moreira Praca, G.; Viana Soares, V.; Alves da Silva Matias, C. J.; da Costa, I. T.; Greco, P. J. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2015)
Soccer performance is multifactorial and is characterized by the interaction of technical, tactical, physical, physiological, and psychological components; however, few studies have investigated the direct relationship between these components in soccer players. The aim of this study was to evaluate the correlation between tactical performance indices (offensive and defensive) and passing, dribbling and shooting technical skills. The FUT-SAT test was used to evaluate tactical behavior and the General Soccer Ability Skill Test Battery to assess technical performance. The Shapiro-Wilk normality test and Spearman`s correlation coefficient were used for statistical analysis. A low correlation was observed between tactical indices (offensive and defensive) and technical skills (shooting, pass and dribbling). Low correlations were also found between the dribbling skill and penetration/width and length with the ball, and between the shot on goal skill and shooting on goal during the game. These results indicate a gap between the knowledge of "how to do it", i.e., technical skills, and the knowledge of "what to do", i.e., tactical knowledge. This gap highlights the need to improve the assessment of technical skills, which should also occur in the game context, such as small-sided games. We conclude that offensive and defensive tactical performance is poorly correlated with passing, dribbling and shooting technical skills in youth soccer players.